Experimental investigation of the tensile and modal properties of epoxy based symmetric interlayer glass/carbon hybrid composites. (1st February 2022) - V Pujar, Nagabhushan; Nanjundaradhya, N V; Sharma, Ramesh S
Abstract: Interlayer hybrid composites can be tailored for enhanced strength and stiffness. Research on enhancing the mechanical properties of Interlayer hybrid composites is being explored by varying fiber orientations, layup sequence, different type of fiber materials. The objective of this work is to investigate the effect of stacking sequence of the high modulus carbon fibers on the tensile and modal properties of symmetric glass/carbon fiber interlayer composite. The interlayer hybrid composites were fabricated for different stacking sequence of carbon fibers using hand layup technique. Tensile strength and modulus were evaluated as per ASTM 3039 standard. Experimental modal analysis was carried out for two boundary conditions (Free-Free and Cantilever). The modal properties such as natural frequency, mode shapes and damping were studied. The results show that interlayer hybridizations by using low & high modulus fibers along with their stacking sequence about the neutral axis of the laminate have significant influence on the tensile and modal properties. Interlayer hybridization technique offers the potential to provide better mechanical and modal properties in design of high-performance composites.